Extension of  Cut Analysis for Trapezoidal Fuzzy Number in Flow Shop Scheduling Models - S. Chandrasekaran, K. Kripa (Design Engineering, 2021)
This paper deals with extension of a cut analysis for trapezoidal membership function in the context of Fuzzy Sequencing model. The average high ranking (AHR) formula is being extended for trapezoidal fuzzy number (TrFN) and the same is used for defuzzify the processing time of the jobs expressed as TrFN. The approach is illustrated with the aid of numerical example.